Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Sure, let's solve this step-by-step. We're given the function [tex]\( f(x) = 7x - 1 \)[/tex]. We need to evaluate and simplify the expressions for [tex]\( f(a) \)[/tex], [tex]\( f(a+h) \)[/tex], and [tex]\(\frac{f(a+h)-f(a)}{h} \)[/tex].
1. Evaluate [tex]\( f(a) \)[/tex]:
Substitute [tex]\( x = a \)[/tex] into the function [tex]\( f(x) = 7x - 1 \)[/tex]:
[tex]\[ f(a) = 7a - 1 \][/tex]
Therefore,
[tex]\[ f(a) = 7a - 1 \][/tex]
2. Evaluate [tex]\( f(a+h) \)[/tex]:
Substitute [tex]\( x = a + h \)[/tex] into the function [tex]\( f(x) = 7x - 1 \)[/tex]:
[tex]\[ f(a + h) = 7(a + h) - 1 \][/tex]
Simplify the expression:
[tex]\[ f(a + h) = 7a + 7h - 1 \][/tex]
Thus,
[tex]\[ f(a + h) = 7a + 7h - 1 \][/tex]
3. Simplify [tex]\(\frac{f(a+h) - f(a)}{h} \)[/tex]:
First, find the difference [tex]\( f(a+h) - f(a) \)[/tex]:
[tex]\[ f(a+h) - f(a) = (7a + 7h - 1) - (7a - 1) \][/tex]
Simplify the numerator:
[tex]\[ f(a+h) - f(a) = 7a + 7h - 1 - 7a + 1 \][/tex]
[tex]\[ f(a+h) - f(a) = 7h \][/tex]
Now, divide by [tex]\( h \)[/tex]:
[tex]\[ \frac{f(a+h) - f(a)}{h} = \frac{7h}{h} \][/tex]
Simplify the expression:
[tex]\[ \frac{7h}{h} = 7 \][/tex]
Thus,
[tex]\[ \frac{f(a+h) - f(a)}{h} = 7 \][/tex]
So the simplified answers are:
[tex]\[ f(a) = 7a - 1 \][/tex]
[tex]\[ f(a+h) = 7a + 7h - 1 \][/tex]
[tex]\[ \frac{f(a+h) - f(a)}{h} = 7 \][/tex]
1. Evaluate [tex]\( f(a) \)[/tex]:
Substitute [tex]\( x = a \)[/tex] into the function [tex]\( f(x) = 7x - 1 \)[/tex]:
[tex]\[ f(a) = 7a - 1 \][/tex]
Therefore,
[tex]\[ f(a) = 7a - 1 \][/tex]
2. Evaluate [tex]\( f(a+h) \)[/tex]:
Substitute [tex]\( x = a + h \)[/tex] into the function [tex]\( f(x) = 7x - 1 \)[/tex]:
[tex]\[ f(a + h) = 7(a + h) - 1 \][/tex]
Simplify the expression:
[tex]\[ f(a + h) = 7a + 7h - 1 \][/tex]
Thus,
[tex]\[ f(a + h) = 7a + 7h - 1 \][/tex]
3. Simplify [tex]\(\frac{f(a+h) - f(a)}{h} \)[/tex]:
First, find the difference [tex]\( f(a+h) - f(a) \)[/tex]:
[tex]\[ f(a+h) - f(a) = (7a + 7h - 1) - (7a - 1) \][/tex]
Simplify the numerator:
[tex]\[ f(a+h) - f(a) = 7a + 7h - 1 - 7a + 1 \][/tex]
[tex]\[ f(a+h) - f(a) = 7h \][/tex]
Now, divide by [tex]\( h \)[/tex]:
[tex]\[ \frac{f(a+h) - f(a)}{h} = \frac{7h}{h} \][/tex]
Simplify the expression:
[tex]\[ \frac{7h}{h} = 7 \][/tex]
Thus,
[tex]\[ \frac{f(a+h) - f(a)}{h} = 7 \][/tex]
So the simplified answers are:
[tex]\[ f(a) = 7a - 1 \][/tex]
[tex]\[ f(a+h) = 7a + 7h - 1 \][/tex]
[tex]\[ \frac{f(a+h) - f(a)}{h} = 7 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.